Predictors of returning for second round screening at a population based mammographic screening programme in Melbourne, Australia. Issue 1 (February 1997) - Cockburn, J; Schofield, P; White, V; Hill, D; Russell, I
Abstract : OBJECTIVE: To examine factors associated with returning for second round mammography screening. SETTING: This was a population based mammographic screening programme in Melbourne, Australia. DESIGN: A cohort design was used whereby 668 women were interviewed before the screening programme began and attendance for both first and second round screening was ascertained from programme records. The cohort sample was drawn from two regions of a defined area (close to and distant from the screening centre). MAIN RESULTS: Of the 315 women who attended for first round screening, 75% from the proximal sample and 70% from the distal sample returned for second round screening. Attendance at the second round was predicted by the following: the method of recruitment for first round screening, with women who required a letter of invitation and a reminder being less likely to reattend than those who initially attended in response to a community campaign (OR = 0.34; CI 0.19, 0.61); mammographic history before the initial screen, with women who reported previous diagnostic mammography being more likely to reattend than those who did not (OR = 2.97; CI 1.01, 8.9); stated intention of attending for the initial screen, with those with weakest intention of attending for their first round being less likely to attend for second round (OR = 0.44; CI 0.23, 0.85); and increasing scores on a scale that measured preventive orientation to health (OR = 1.24; CI 1.02, 1.50). CONCLUSION: Our findings corroborate other findings of reduced long term attendance for screening from people who are "reluctant participants" initially.